2009
DOI: 10.1111/j.1398-9995.2009.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Asthma Control Test and airway inflammation evaluation in asthmatic children

Abstract: This study confirms and expands the concept that C-ACT is complementary to, but not a substitute for, other markers of disease control in asthmatic children, especially in the context of follow-up visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 35 publications
4
43
0
1
Order By: Relevance
“…[18][19][20] For children, the cACT has more validation data than other tools that target children with asthma. [37][38][39] Also, the populations used in the validation studies vary between tools. For instance, in the United States, studies have included mostly white patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] For children, the cACT has more validation data than other tools that target children with asthma. [37][38][39] Also, the populations used in the validation studies vary between tools. For instance, in the United States, studies have included mostly white patients.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] In the developmental study, Liu et al 36 reported that the cACT overall score discriminated between patients who differ in the specialists' rating of asthma control. Similarly, Chen et al 37 reported that mean cACT scores were significantly lower among patients with poor asthma control as compared with those who were well controlled according to specialists' rating.…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is no general consensus about correlation between F ENO and respiratory function in children. 2,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] The main limitation of our study is the retrospective design. We gathered data from the subjects' medical documentation, which could partly have influenced the accuracy of our results.…”
Section: Discussionmentioning
confidence: 99%
“…14 -16 The ACQ and ACT have been validated for use as self-administered instruments in person, at home, by telephone, and by Internet tracking. 6,17 Poor asthma control, as measured by the commonly used composite scores, is associated with reduced lung function and elevated exhaled nitric oxide fraction 5,18 (discussed later in the article). Studies have shown that changes in these composite scores reflect changes in the overall clinical assessment of asthma control by physicians and the need to step-up therapy.…”
Section: Composite Asthma Scoresmentioning
confidence: 99%